MASYARAKAT MINANGKABAU PASCA-PRRI: Dalam cerpen Ketika Jendral Pulang karya Khairul Jasmi - Ronidin, Ronidin (English Department FBS UNP, 2010)
This article describes the influence of PRRI events (Revolutionary Government of the Republic of Indonesia) on the life of the people of West Sumatra (Minangkabau) in the short story